Associations between Wyoming third grade body index and school food environment - Hammond, Marilyn, author; Keefe, Thomas, advisor; Butler, Lesley, committee member; Bellows, Laura, committee member; Busacker, Ashely, committee member (Colorado State University. Libraries, 2012)
Overweight and obesity, conditions defined as excess body fat, are associated with increased risk of physical and mental health issues in children, including cardiovascular and pulmonary issues, developmental, learning, behavioral and emotional problems, as well as increased risk of becoming an obese adult. The prevalence of obesity has more than tripled in American children in the past three decades. If this trend is not reversed, it will shorten and diminish the quality of life of those affected, as well as increase already burgeoning medical costs. As most children in Wyoming spend much of their time in school; so, this study was designed to identify potential association of the school food environment policies and practices on the risk of being overweight or obese among children in the schools. This study utilized a subset of data from third grade students from the Wyoming Department of Health's Community and Public Health Division 2009-2010 Oral Health Survey who agreed to participate in the body mass index (BMI) screening. Out of 42 participating schools, information needed to calculate their BMI was obtained for 1570 children. Information on school policies and practices was gathered from the Wyoming Department of Education, the Department of Defense, the United States Department of Agriculture Foods Distribution Program, the U.S. Census Bureau, individual school nurses, school district business directors, school district food service directors and school lunch menus. Based on application of multiple logistic regression methods, two models were developed independently to describe the relationship of (1) overweight and (2) obesity with school characteristics in this study. The participation rate of schools among sampled was 76.4%, and the participation rate of students in those schools was 78.0%. The percent of obese children was 15.5%, and the percent of overweight (including obese) children was 31.3%. Children at schools who used the Department of Defense's Fresh Fruit and Vegetable Program (OR=0.78, 90% C.I.: 0.56, 1.08) or served fresh fruit or raw vegetables daily in school lunches (OR=0.74, 90% C.I.: 0.54, 1.00) were less likely to be overweight. Similarly, children at schools who used the United States Department of Agriculture's Fresh Fruit and Vegetable Program (OR=0.68, 90% C.I.: 0.46, 1.00) or served fresh fruit or raw vegetables daily in school lunches (OR=0.68, 90% C.I.: 0.44, 1.00) were less likely to be obese. The results of this study suggest that increasing the availability and variety of fruits and vegetables, especially fresh fruits and vegetables, in Wyoming schools may reduce the risk of children at those schools being overweight or obese. School characteristics identified in this study may assist in identifying children at higher risk for being overweight or obese. These results should be used by the Wyoming Department of Health to assist in future research, provide information for targeted interventions and improve the health of Wyoming children.
Keywords: children; elementary; food; obesity; overweight; school